Gênero é o que importa: Determinantes do trabalho doméstico n\~ao remunerado no Brasil - Luana Pinheiro; Marcelo Medeiros Coelho de Souza; Joana Sim\~oes Costa; Ana Luiza Neves de Holanda Barbosa (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– We examine how position in the life course, time availability, relative resources within a family, and compensatory response (gender display) determined gender inequalities in reproductive work among Brazilian couples in 2019 using panel data from the Brazilian National Household Continuous Survey 2019 (PNAD Contínua 2019). We found that the position in the life course has a much stronger effect on women, with children extending the time spent in domestic labor - although this time decreases as the age of the children increases, the impact of children on women is twice that on men. Taking care of the elderly increases the reproductive workload of women but has no effect for men. In terms of time availability, the trade-off between paid and unpaid work is strong for women and very weak for men. Richer families use their income to acquire goods and services that reduce their domestic work, but the substitution effect is stronger among women. Within a couple, the ability to transform relatively higher financial resources into shorter working hours is determined by conventional gender values. Notably, we found that, even when women are the major income providers of the couples, they behave like traditional women in domestic work. Education is an equalizer of gender relations, but its effect is framed by gender roles and race. Traditional gender values are the most important factor determining reproductive work.
Keywords: J11; J13; J14; J16; J22; Z13; 330; housework; household labor; domestic labor; unpaid work; care; sexual division of labor